2022
DOI: 10.1038/s41598-021-04594-w
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Glycyrrhizic acid ameliorates submandibular gland oxidative stress, autophagy and vascular dysfunction in rat model of type 1 diabetes

Abstract: The burden of diabetes mellitus (DM) and associated complications is increasing worldwide, affecting many organ functionalities including submandibular glands (SMG). The present study aims to investigate the potential ameliorative effect of glycyrrhizic acid (GA) on diabetes-induced SMG damage. Experimental evaluation of GA treatment was conducted on a rat model of type I diabetes. Animals were assigned to three groups; control, diabetic and GA treated diabetic groups. After 8 weeks, the SMG was processed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Diabetes mellitus (DM) is a complex chronic metabolic disease whose incidence is escalating globally (1,2). Type 1 DM (T1DM) is caused by progressive T cell-mediated immune damage of pancreatic b cells resulting in persistent hyperglycemia (3).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a complex chronic metabolic disease whose incidence is escalating globally (1,2). Type 1 DM (T1DM) is caused by progressive T cell-mediated immune damage of pancreatic b cells resulting in persistent hyperglycemia (3).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the results of this study, SOD and CAT activities were significantly reduced in the neurodegenerative disease model, accompanied by elevated levels of the lipid peroxidation product and increased expression of COX2 and iNOS, whereas GL increased antioxidant enzyme activity, inhibited lipid peroxidation, and attenuated elevated levels of COX2 and iNOS, these results suggest that the neuroprotective effects of GL are attributed to its potent antioxidant and anti‐inflammatory properties 25 . Another study showed that diabetes caused an increase in malondialdehyde levels and a decrease in SOD and glutathione in submandibular gland tissue, however, GL reduced oxidative stress damage in submandibular gland tissue by restoring the levels of oxidative stress markers 26 …”
Section: Discussionmentioning
confidence: 93%
“…25 Another study showed that diabetes caused an increase in malondialdehyde levels and a decrease in SOD and glutathione in submandibular gland tissue, however, GL reduced oxidative stress damage in submandibular gland tissue by restoring the levels of oxidative stress markers. 26 The balance between oxidation and antioxidation is essential for maintaining healthy cartilage tissue, and disruption of this balance leads to OA pathogenesis and progression, with multiple enzymes and factors involved in the antioxidant process. In joint tissues, excessive oxidative stress not only causes abnormal bone and cartilage metabolism, leading to destruction of joint structures, but also stimulates cells in synovium, such as synovial cells and nerve cells, which are the main cause of pain and muscle symptoms during OA progression.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizic acid (GA), a bioactive ingredient of licorice, has been demonstrated to exhibit immunoregulatory, antioxidant, anti-inflammatory, and antiviral properties in various diseases ( Li et al, 2021a ; Asseri et al, 2022 ; Qian et al, 2022 ). Zhao et al found GA inhibited the production of TNF-α, IL-1β, and IL-6, and suppressed oxidative stress and apoptosis through activation of the extracellular signal-regulated kinase (ERK)/NF-κB signaling pathway in LPS and CLP-induced septic rats ( Zhao et al, 2016a ; Zhao et al, 2016b ).…”
Section: Therapeutic Approaches In Sepsis-induced Acute Kidney Injurymentioning
confidence: 99%